ANALISIS KEBIJAKAN PEMERINTAHAN DAERAH DALAM PEMBANGUNAN WISATA BUDAYA BERBASIS KEARIFAN LOKAL DI KABUPATEN CIAMIS - Asep Nurwanda; Elis Badriah (Sekolah Tinggi Pariwisata Mataram, 2023)
The site is an area where ancient objects are found. One of the Sundanese cultural sites based on local wisdom is the Ciung Wanara site culture located in Cijeungjing District, Ciamis Regency. The Ciung Wanara site is the site of the Ciungwanara story from the Hindu-Buddhist period. There are many ancient cultural remains at this site. The various heritages contained in this site are local cultural assets which are part of the history of Ciamis Regency. The tendency of today's modern society is to forget the heritage of these local cultural wisdoms, especially the inheritance from local ways of thinking that have the best values ​​which are the norms of their society. The results of the study found that there were about nine pieces of art that had the shape of a square or rectangular arrangement of stones with standing stones and flat stones spread out. Basically there are two types of shapes, namely rectangles and circles, standing stones and flat stones lying on the ground and have philosophical meanings. The method used in this study is a qualitative research with a descriptive design with the process of collecting and analyzing data. Research by collecting data descriptively is research that is carried out solely on the basis of facts and phenomena that are indeed empirically alive in the speakers - the speakers, so that what is produced is in the form of language descriptions that can be said to be portrait-like in nature.